Setting sodium targets for pre-packaged foods in China — an exploratory study - Zhang, Puhong; Zhang, Jiguo; Rosewarne, Emalie; Li, Yuan; Dong, Le; He, Feng J.; Brown, Mhairi; Pettigrew, Simone; Yamamoto, Rain; Nishida, Chizuru; Liu, Aidong; Yang, Xiaoguang; et al. (Frontiers in Nutrition, 2023)
Setting sodium targets for pre-packaged food has been a priority strategy for reducing population sodium intake. This study aims to explore the attitudes and considerations of researchers and key stakeholders towards implementing such policy in China. An exploratory study comprising a survey and a focus group discussion was conducted among 27 purposively selected participants including 12 researchers, 5 consumers, 4 administrators, 3 industry association representatives and 3 food producers. The survey/ discussion covered the key questions considered when developing/promoting sodium targets. Free-text responses were manually classified and summarized using thematic analysis. Two-thirds of the participants supported target-setting policy. Researchers and administrators were most supportive, and food producers and associations were least supportive. Adapted WHO food categorization framework was well accepted to underpin target-setting to ensure international comparability and applicability for Chinese products. Maximum values were the most agreed target type. The WHO benchmarks were thought to be too ambitious to be feasible given the current food supply in China but can be regarded as long-term goals. Initially, a reduction of sodium content by 20% was mostly accepted to guide the development of maximum targets. Other recommendations included implementing a comprehensive strategy, strengthening research, engaging social resources, establishing a systematic monitoring/incentive system, maintaining a fair competitive environment, and developing a supportive information system. Target-setting policy was acceptable by most stakeholders and should be implemented alongside strategies to reduce discretionary salt use. Our findings provide detailed guidance for the Chinese government when developing a target-setting strategy. The methods and results of this study also provide meaningful references for other countries to set sodium targets for pre-packaged foods and implement other salt reduction strategies simultaneously.